Caracterização físico-química das polpas do fruto do sapotizeiro (Manilkara sapota, L.). - Soares, Gabriella Greyce Gomes (2018)
The sapodilla tree is native to southern Mexico and Central America, with great adaptation to Brazilian soils, especially in the Northeast. Its fruits popularly known as sapota and sapoti, belong to the same family (Sapotaceae) and belong to the species (Manilkara sapota). They are exotic fruits, little studied until today. This work aimed to characterize the physicochemical composition of the pulps of different types of sapodilla (Manilkara sapota) fruit, sapota and sapoti. Sapota fruits were collected in different regions of the Northeast, with sapota fruits grown in the city of João Pessoa, called Sapota-PB, sapota fruits cultivated in the city of João Pessoa, named Sapoti-PB. of sapoti from the city of Parnaíba, in the state of Piauí, named Sapoti-PI. The physicochemical characterization showed high water activity (0.99), total soluble solids and ratio (mean 20.13 and 148.33, respectively), which indicated that they are sweet fruits, low titratable acidity (0.14 g / 100g citric acid) and pH 6.05. In the organic acid profile analysis, citric, tartaric, malic, succinic, formic and acetic acids were detected. The centesimal composition showed high humidity (around 74.25%), low ash content (around 0.50%) and high sugar content, analyzed by classical titration methods and high performance liquid chromatography. efficiency, which was identified in greater quantity in the Sapoti-PI sample. It can be concluded that sapotizeiro fruits are highly perishable, with low acidity, but they have high sugar content, mainly the Sapoti-PI sample, which makes the fruits indicated for sugar products processing.